Researching Of Oil Extraction Process from Pumpkin Seeds Using Non-Conventional Method of Energy Exposure - Djurayev Kh.F.; O`ktamova Sh.H. (Global Scientific Publishing, 2022)
Pumpkin seed oil is taken from pumpkin seeds either through a cold pressing or through pressing the seeds using heat (hot pressing). Pumpkins can contain up to 100 seeds, which can be further processed with or without their shells. Pretreated seeds are fed into a press. Pressing can efficiently remove the oil both in the cold press process and also from roasted pumpkin seeds. Products from this process include pumpkin seed oil and high quality pumpkin seed press cakes. In Styria, a very specific process is used. First the seeds are washed, then dried at approx. 50°C, ground and mixed with water and salt into slurry, and then roasted so that the water evaporates. The roasting process separates the protein and oil contained in the seeds. Finally, the slurry is fed into a press. Pumpkin seed oil also purportedly has a beneficial impact on prostate adenoma in its initial states, an effect which nevertheless has not yet been proven, along with several other healing powers attributed to this oil. It is also supposed to have a detoxifying effect and decrease blood pressure, thereby helping prevent heart and circulatory problems
Keywords: method; processing; separation; extraction technique